Cu and Zn stable isotopes in suspended particulate matter sub-fractions from the northern Bay of Biscay help identify biogenic and geogenic particle pools. (15th July 2022) - Araújo, Daniel F.; Knoery, Joël; Briant, Nicolas; Ponzevera, Emmanuel; Mulholland, Daniel Santos; Bruzac, Sandrine; Sireau, Teddy; Chouvelon, Tiphaine; Brach-Papa, Christophe
Abstract: Marine suspended particulate matter (SPM) plays a pivotal role in the marine biogeochemical cycling of trace elements. This study investigates metal distributions and copper (Cu) and zinc (Zn) stable isotope ratios in different size fractions of SPM from two sampling stations on the inner continental shelf of northern Bay of Biscay (NE Atlantic), a zone highly influenced by the macrotidal Loire estuary, the outlet of a major European river. The objective of this study is to test stable isotopes as tools to infer the origins of particles and their formation processes, and to infer relevant Cu and Zn biogenic pools involved in marine trophic transfers of these metals. SPM samples were nearly quantitatively mineralized (i.e., without HF) to determine metals and Cu and Zn isotopes in their more labile and reactive phases. Their δ 65 CuSRM-976 values ranged from −0.45 to +0.51‰, with higher Cu concentrations accompanying particle size decreasing. The δ 66 ZnJMC-Lyon values in SPM sub-fractions varied from +0.14 to +0.76‰, and were uncorrelated to both Zn concentrations and particle size. Compared to larger size fractions, increased Al and Fe levels (proxies for terrigenous materials) and enrichments in lighter Cu and Zn isotopes observed in the smaller size SPM sub-fractions suggest that a major proportion of SPM Cu and Zn is associated with geogenic particles. Conversely, the relative enrichment of heavy isotopes in coarser particles is attributable to an increase of Cu and Zn metabolically incorporated into biogenic organic particles (e.g., plankton), and by surface adsorption onto organic detrital particles. The higher δ-values attributed to biogenic particles likely represents the isotope composition of the local marine organic matter available to primary consumers like filter-feeders (oysters). Thus, this study shows that targeting particles of specific size classes allows to identify relative dominances of biogenic and geogenic carrier phases. Identifying these pools and their isotopic composition may help to track Cu and Zn transfers through marine food-web in future studies. Graphical abstract: Image 1 Highlights: Cu and Zn isotopes in different particle sizes of SPM from Biscay Bay. Four size fractions (63–250; 250–500; 500–1000; and >2000 μm) were target. Isotopes help identify geogenic and biogenic pools in SPM sub-fractions. Geogenic pools are enriched in the light and biogenic pools in the heavy isotopes. Isotopes in SPM sub-fractions may help to constrain food-web metal transfers.